Avaliando os benefícios de estratégias imaginativas e da prática de lembrar em tarefas de recordação com pistas - Ana Luísa Santiago da Silveira Fonseca (2024)
Retrieval practice it’s a learning strategy that has been frequently studied within the fields of cognitive neuroscience and cognitive psychology. Many studies utilized different strategies for efficiency comparison, as concept mapping, rereading or note taking. Being rereading the primarily strategy of choice for comparison. Albeit, only a few studies utilized effective different strategies for efficiency comparison, like imagination or deep processing techniques. To investigate this, one experiment involving 52 participants (18 to 36 years old) was conducted. Here, we compared retrieval practice, sentence formation (imagination) and restudy as study strategies for word pairs. At the first stage of the experiment, the participantes performed a rereading, retrieval practice and sentence formation task and at the end of the experiment, the participants performed a cue recall test, and we compared their performances to evaluate which strategy enhanced episodic memory retention. The results we obtained showed us that retrieval practice obtained a greater performance than restudy, while imagination obtained a greater performance than retrieval practice and restudy. These results demonstrates that even simple tasks can improve memory retention. We also requested the participants to evaluate which strategy they believed have helped them recall the word pairs and provided feedback with the percentage of correct answers within each strategy. The similar findings suggests that retrieval practice and imagination may share similar mechanisms as demonstrated by previously research on cognitive psychology, which corroborates with constructive episodic simulation account. We suggest that constructive episodic simulation enhances episodic memory retention, regardless of how the constructive episodic simulation was conducted.